Strategi Komunikasi Pemasaran PT. ECC Dalam Meningkatkan Brand Awareness Melalui Media Sosial Instagram @Ecc.Co.Id - Dian Nata, Albi; Nurussa'adah, Erfina (Universitas Pahlawan Tuanku Tambusai, 2024)
This study examines the marketing communication strategies implemented by PT. ECC to increase brand awareness through Instagram @ecc.co.id using the 7P marketing communication mix theory. The research employs a descriptive qualitative method with purposive sampling techniques, conducted through interviews with the ECC director and the digital marketing team, as well as online data from screenshots of ECC's social media and website. The findings reveal that ECC applies the 7P marketing communication mix strategy, which includes: 1) Its key products are online job listings, OPA, Career Learning, and counseling, with an online CV creation feature. 2) Product prices range from free to several million rupiah. 3) Promotion is mainly done through Instagram, utilizing creative content such as video reels and persuasive captions. 4) Online channels include the ecc.co.id website and an offline office in Yogyakarta. 5) Participants include the digital marketing team and DGV to create Instagram content. 6) The process involves the digital marketing and design teams posting 4-5 pieces of content per day. 7) The office has a minimalist design, and the website ecc.co.id plays an essential role.